Traditional use Antifungal, Antibacterial of local Iraqi Medicinal Plants: in Review - Zahraa Kareem Naief Kadhim; Eman Abbas Halbous Mutlk; Worood Khtan Ibrahim Issa; Mansour Mushab Mujed Awad; Yousif kadem denh rahyj; Noor Ayad Qasim Mohsen (Genius Journals, 2024)
The Present review was conducted to explain the role of Iraqi medicinal plants in traditional medicine. This review is an attempt to highlight the traditional uses of Iraqi medicinal plants. Plants produce chemical compounds as part of their normal metabolic activities. Plants are a valuable source of a wide range of secondary metabolites, which are used as pharmaceuticals, agrochemicals, flavours, fragrances, colours, biopesticides and food additives
Keywords: Antifungal; Antibacterial; Medicinal Plants